The Man Who Never Returned - Quinn, Peter (Peter A.) (Book collections on Project MUSE., 2010)
Judge Joe Craters disappearance in 1930 spawned countless conspiracy theories and captured the imagination of a nation caught in the grip of The Depression. Fifteen years later, Fintan Dunne the detective encountered in Quinns novel Hour of the Cat, recently retired and bored, answers a summons to New York where he is asked to solve the old case for a newspaper magnate only interested in making a profit from the story.